Perfil virulento, disseminação fenotípica e distribuição espacial e sazonal de Campylobacter jejuni isoladas de carcaças de frango no Brasil - Peres, Phelipe Augusto Borba Martins (2020)
Campylobacter is among the four pathogens most incriminated in foodborne diarrheal diseases worldwide and C. jejuni is the most involved species in campylobacteriosis. Among the sources of illness to humans, the consumption of undercooked chicken meat has been highlighted, and for this reason, in addition to public health, there is also an impact on the economy. The dissertation was divided into two chapters. The first one describes the general considerations, reporting relevant information to the reader's context on the proposed theme, and also the general and specific aims of the study. The second chapter records the epidemiological study of 359 strains of C. jejuni isolated from 114 chilled chicken carcasses, slaughtered in establishments registered under federal inspection, and qualified for internal and external trade between the years 2017 and 2018. The isolations were performed in an official laboratory of the Ministry of Agriculture, Livestock and Supply using the methodology proposed by ISO 10272-1: 2017 (ISO, 2017) for the genus and the mass spectrometer (MALDI TOF®) for the identification of the species. The strains were evaluated by conventional PCR for a panel of 14 virulence genes categorized as: i) biofilm formation - flaA (motility) and luxS (quorum-sensing mechanism); ii) secretion systems - cdtABC (distensive cytotoxin secretion) and hcp (type VI secretion system; iii) invasion and colonization - cadF (intracellular colonization), ciaB (cell invasion) and pldA (invasion/colonization); iv) adaptation to stress - dnaJ (thermotolerance), htrA (aid in growth under stress) and cbrA (resistance to osmotic shock); and v) induction of Guillain-Barré Syndrome - cstII (SGB) and neuA (SGB). The results were used to create profiles, determine the variability, virulence, and multivirulence indexes of the strains. The spectra obtained in the identification of the species by mass spectrometry, were used for the construction of a dendrogram, to evaluate the distribution of the strains.